Law and constitutional change / edited by David Capper, Conor McCormick, N. M. Dawson. - Capper, David; McCormick, Conor; Dawson, Norma (Cambridge University Press, 2025)
A collection of some of the best papers presented at the 25th British Legal History Conference at Queen's University Belfast in July 2022, Law and Constitutional Change examines the role that law plays when countries experience a major constitutional upheaval. It examines the interaction of law and politics in history across different legal jurisdictions with different legal traditions. The theme of the conference was 'Law and Constitutional Change' and was inspired by the decade of anniversaries in Ireland (2012-2023) commemorating events from a century ago that began with the Home Rule Crisis and ended with the partition of the country. It studies the changes that occurred at that time in a wider British and Irish as well as international context, with a view to deepening understanding of contemporary debates such as those surrounding Brexit and its longer-term implications. This title is also available as open access on Cambridge Core.